The Sino-Indian border dispute : analysing the Galwan conflict and prospects for a peaceful resolution - Rao, Sumanshu; Garlick, Jeremy; Veselá, Zuzana; Vysoká škola ekonomická v Praze. Fakulta mezinárodních vztahů (2024)
Since their founding, China and India, Asia's growing powers, have seen their unresolved border dispute become a constant source of friction, leading to repeated military confrontations and diplomatic clashes. As such was the incident in the Galwan Valley in 2020, which marked the first fatality in almost four decades, however cooperation among two Asian Giants have been growing even during the conflict. The thesis, therefore, attempts to answer a research questions "what are the reasons behind the coexistence of conflict and cooperation between India and China". Using the theoretical framework of realism and complex interdependence thesis has tried to answer the research question. Sino-Indian border disputes have historical roots dating back to British Empire, and cooperation started ever since they gained independence. The relations between India and China have been bittersweet, fought a war and also showed interest in cooperation. However, the Galwan incident is has worsened the relations but cooperation on economic level and also on other shared interests have been constant, which narrates that the two emerging powers in world order are hopefull on cooperating with each other. India and China need to address issues that fuel there deep distrust to solidify there relations and also to maintain the regional stability. Their future of cooperation is not the easiest one but fostering mutual trust and nurturing economic interdependence can pave their path towards a peaceful and prosperous future.
Vedoucí práce: Jeremy Alan Garlick
Bakalářská práce (Bc.)—Vysoká škola ekonomická v Praze. Fakulta mezinárodních vztahů, 2024
Obsahuje bibliografii
Textový (vysokoškolská kvalifikační práce)
Rok obhajoby 2024
Způsob přístupu: Internet
Keywords: international and diplomatic studies [obor bakal. práce]; bakalářské práce; bachelor's theses